Makna Metafora Ontologis dalam Genbaku Shishū Karya Tōge Sankichi: Kajian Semantik - Diaji, Jahroo Najah; Karnawati, Rita Agustina (KIRYOKU, 2025)
This study investigates the types and functions of ontological metaphors in Genbaku Shishū by Tōge Sankichi, focusing on how they represent the physical and psychological impact of the Hiroshima atomic bombing. Using a qualitative method with a stylistic approach and content analysis, the study is grounded in Lakoff and Johnson’s conceptual metaphor theory. Ontological metaphors found in the poems were categorized into five types: thought, event, emotion, inanimate object, and body part. A total of 192 lines containing ontological metaphors were identified. Body part metaphors are the most dominant (107 lines), followed by inanimate objects (60), emotions (13), events (8), and thoughts (4). These metaphors express abstract experiences—pain, trauma, and memory—as concrete entities, enhancing emotional depth and imagery. The study concludes that ontological metaphors strengthen the poetic expression of historical trauma and deepen readers’ engagement with the victims’ lived experiences.